Corporate Governance in Korea - Nam, Il Chong; Kim, Joon-Kyung; Kang, Yeongjae; Sung Wook Joh; Sung Wook Joh; Jun-Il Kim; Jun-Il Kim (Corporate Governance in Asia: A Comparative Perspective, 2001)
Poor corporate governance was identified as one of the root causes of the recent Asian financial crisis. The absence of effective disciplines on corporate managers, coupled with complicated and opaque relationships between corporations, their owners and their finance providers, affected severely investors’ confidence in the region’s corporate sectors. Economies that took early steps to improve corporate governance have been recovering from the crisis at a more rapid pace than those who have not addressed this issue. The Asian crisis showed that good corporate governance is important not only for individual corporations to raise capital but also for an economy to achieve sustainable growth. This publication includes papers submitted to the "Conference on Corporate Governance in Asia: A Comparative Perspective" held in Seoul in March 1999. These papers describe vividly the corporate governance practices in the region and the recent changes largely prompted by the crisis. Also included are papers on corporate governance in major OECD countries, which serve as a good source of comparative information on this issue. This review is part of the OECD's ongoing co-operation with non-Member economies around the world.